Influence of conspiracy theories and distrust of community health volunteers on adherence to COVID-19 guidelines and vaccine uptake in Kenya. - Edward Mugambi Ireri; Marion Wanjiku Mutugi; Jean-Benoît Falisse; James Mwirigi Mwitari; Lydia Kemunto Atambo (Public Library of Science (PLoS), 2023)
Public trust is key for compliance to government protocols in times of health mitigating COVID-19 measures and its vaccination initiative, and thus understanding factors related to community health volunteers (CHVs) trusting the government and conspiracy theories is vital during the COVID-19 pandemic. The success of universal health coverage in Kenya will benefit from the trust between the CHVs and the government through increased access and demand for health services. This cross-sectional study collected data between 25 May to 27 June 2021 and it involved CHVs sampled from four counties in Kenya. The sampling unit involved the database of all registered CHVs in the four counties, who had participated in the COVID-19 vaccine hesitancy study in Kenya. Mombasa and Nairobi (represented cosmopolitan urban counties). Kajiado represented a pastoralist rural county, while Trans-Nzoia represented an agrarian rural county. Probit regression model was the main analytical method which was performed using R script language version 4.1.2. COVID-19 conspiracy theories weakened generalised trust in government (adjOR = 0.487, 99% CI: 0.336-0.703). Banking on COVID-19 related trust in vaccination initiatives (adjOR = 3.569, 99% CI: 1.657-8.160), use of police enforcement (adjOR = 1.723, 99% CI: 1.264-2.354) and perceived risk of COVID-19 (adjOR = 2.890,95% CI: 1.188-7.052) strengthened generalised trust in government. Targeted vaccination education and communication health promotion campaigns should fully involve CHVs. Strategies to counter COVID-19 conspiracy theories will promote adherence to COVID-19 mitigation measures and increase vaccine uptake.